TINDAK TUTUR DALAM PRAKTIK MENGAJAR MAHASISWA PENDIDIKAN PROFESI GURU (PPG) UNIVERSITAS PGRI ADI BUANA SURABAYA - Novia Vernawati; Agung Pramujiono (Universitas PGRI Adi Buana Surabaya, 2020)
This research has a background in the function of language as a communication tool. Every human being has a communication tool used in everyday life. Humans use language to express ideas, thoughts, opinions, and interact with each other.The purpose of this study is to describe speech acts in teaching practices for students of Teacher Professional Education PGRI Adi Buana University Surabaya. The theory used in this study is the theory of speech acts from Searle. The method used in this research is descriptive qualitative. Data collection techniques using documents. The data analysis techniques used are data reduction, coding, and data presentation. The results of the study found there are directive speech acts and expressive speech acts. The directive speech acts consist of six types, namely the request directive speech act, the question directive speech act, the directive speech act of the directive, the prohibition directive speech, the directive act of giving permission and the non-directive advice directing. Whereas the expressive speech act function consists of expressive greetings of congratulations, expressive expressions of thanks, expressive expressions of criticism, expressive expressions of praise, expressive insinuations and expressive expressions of apology.